Interference control and selective attention ability among children with Auditory Processing Disorder (APD) - Sulaiman, Nur Hafizah; Dzulkarnain, Ahmad Aidil Arafat; Maamor, Nashrah; Rahmat, Sarah (2021)
Introduction: In everyday life listening environment, the bottom-up auditory processing system and the top-down processing of executive functions work closely to suppress the irrelevant sound and help to focus on the relevant sound. The executive functions that help to achieve this goal are interference control and selective attention. Considering the importance of these executive functions, this study aimed to investigate the ability in inhibitory control and selective attention among normal and APD children, particularly in the event that attention deficit was also identified together with APD.